2021
DOI: 10.2298/jsc201228028u
|View full text |Cite
|
Sign up to set email alerts
|

A prudent approach for the removal of copper (II) and cadmium (II) ions from aqueous solutions using indigenous Mactra aequisulcata shells

Abstract: In this study, the raw seashells of Mactra aequisulcata, of class Bivalvia and phylum Mollusca were employed as an adsorbent to remove copper (II) and cadmium (II) metal ions from aqueous solution. The characterization of shells was performed using FTIR, EDX and SEM, BET isotherm and point of zero charge (pHpzc). Batch experiments were performed to assess various factors on the biosorption efficiency. Maximum adsorption of both metals ions conveniently found at 0.4 g L-1 adsorbent dose, pH 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The pseudo-1 st order model has also been reported to be the best model for cadmium sorption onto nano-clay/TiO2 composite [25], coco-peat biomass [26], alginate-calcium carbonate composite beads [27], poly(acrylamide-co-sodium methacrylate) hydrogels [28], the bacterium, Salmonella enterica 43C [29], water hyacinth (Eichhornia crassipes) biochar alginate beads [30], zerovalent iron nanoparticles [31] and Mactra aequisulcata shells [32]. On the other hand, the pseudo-2 nd order kinetics model has been reported to be the best model in several other cadmium sorption studies such as sorption of cadmium onto C-4-phenacyloxy-phenylcalix [4], resorcinarene [33], modified palm shell powder [34], chemically modified biomass from Triticum aestivum [35] and several other heavy metals such as the biosorption of Cr(VI) to magnetic iron oxide nanoparticlemulti-walled carbon nanotube [36], Cu(II) adsorption onto functionalized cellulose beads from Tunisian almond (Prunus dulcis) shell [37], the sorption of Zn(II) by Streptomyces ciscaucasicus [38] and other heavy metals [23,[39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The pseudo-1 st order model has also been reported to be the best model for cadmium sorption onto nano-clay/TiO2 composite [25], coco-peat biomass [26], alginate-calcium carbonate composite beads [27], poly(acrylamide-co-sodium methacrylate) hydrogels [28], the bacterium, Salmonella enterica 43C [29], water hyacinth (Eichhornia crassipes) biochar alginate beads [30], zerovalent iron nanoparticles [31] and Mactra aequisulcata shells [32]. On the other hand, the pseudo-2 nd order kinetics model has been reported to be the best model in several other cadmium sorption studies such as sorption of cadmium onto C-4-phenacyloxy-phenylcalix [4], resorcinarene [33], modified palm shell powder [34], chemically modified biomass from Triticum aestivum [35] and several other heavy metals such as the biosorption of Cr(VI) to magnetic iron oxide nanoparticlemulti-walled carbon nanotube [36], Cu(II) adsorption onto functionalized cellulose beads from Tunisian almond (Prunus dulcis) shell [37], the sorption of Zn(II) by Streptomyces ciscaucasicus [38] and other heavy metals [23,[39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the adsorption of heavy metal ions using shells have been reported such as adsorption of Pb and Cu ions using shells (Anadara inaequivalvis) [17], adsorption of Pb, Ni, and Zn using an adsorbent combined pervious concrete and seashell [18], removal of Sr ions from aqueous solution using clam shell (Donax trunculus) [19], adsorption of Pb ions using mussel shell-based adsorbent [20], removal of Cu, Co, and Pb ions using calcined snail shell (Solamen Vaillanti) [21], adsorption of Ni ions on sea shells of Mehdia [22], development of adsorbent combined cement and shells [23], adsorption of Cu, Cd, and Pb ions using calcined golden apple snail shell [24], adsorption of Cu, Zn, Cd, and Ni ions using discarded shells from canning industry [25], adsorption of Cu and Cd ions using indigenous shells (Mactra aequisulcata) [26], and so on. In addition, the following studies have been reported on the application of mechanochemical reactions by ball milling of discarded shells, for example, preparation of nanosized calcium carbonate powder from mollusk shells [27], preparation of high pure calcite powders from oyster shells by combination of mechanochemical and hydrothermal treatments [28], and so on.…”
Section: Introductionmentioning
confidence: 99%